UX writing designing user-centered content - Tham, Jason Chew Kit 1990-; Howard, Tharon W.; Verhulsdonck, Gustav 1975- (Routledge, Taylor & Francis Group, 2024)
This flexible textbook provides an integrated approach to user experience (UX) writing and equips students and practitioners with the essential principles and methods to succeed in writing for UX.The fundamental goal of UX writing is to produce usable and attractive content that boosts user engagement and business growth. This book teaches writers how to create content that helps users perform desired tasks while serving business needs. It is informed by user-centered design, content strategy, artificial intelligence (AI), and digital marketing communication methodologies, along with UX-related practices. By combining writing-as-design and design-as-writing, the book offers a new perspective for technical communication education where UX design and writing are merged to achieve effective and desirable outcomes.Outlining the key principles and theories for writing user-centered content design, this core textbook is fundamental reading for students and early career practitioners in UX, technical communication, digital marketing, and other areas of professional writing
Keywords: Benutzeroberfläche; Design; Benutzerverhalten; Schreiben